On some estimations of the renewal function - Kaminskienė, B. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. А. Каминскеие. Некоторые оценки для функций восстановленияB. Kaminskienė. Kai kurie atstatymo funkcijos įvertinimai